2008
DOI: 10.2135/cropsci2007.05.0262
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Seaweed Extract‐Based Cytokinins and Zeatin Riboside on Creeping Bentgrass Heat Tolerance

Abstract: Heat stress is the primary factor limiting summer performance of creeping bentgrass (Agrostis stolonifera L.) in many temperate to subtropical regions. Seaweed extract (SWE)‐based cytokinins have been used to improve stress tolerance, but their specific effects on creeping bentgrass under supraoptimal temperatures are lacking. This study was designed to determine whether SWE‐based cytokinins affect creeping bentgrass heat tolerance, and to compare effects of SWE‐based cytokinins to those of a trans‐zeatin ribo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
107
0
5

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 176 publications
(122 citation statements)
references
References 29 publications
(52 reference statements)
10
107
0
5
Order By: Relevance
“…The combined capacity of fulvic acids both to chelate nutrients such as Fe and move through membranes has suggested the fulvic acids may play similar roles as natural chelators in the mobilization and transport of Fe and other micronutrients (Bocanegra et al 2006). It has also been suggested that since they have smaller molecular weights, FAs can remain in soil solution even at high salt concentrations and at a wide range of pH (Zimmerli et al 2008;Zhuang et al 2007;Zhang et al 2010;Zhang & Ervin 2008;Zhang & Ervin 2004;Zhang et al 2006). Therefore they have long-lasting potential to interact with plant roots (Varanini and Pinton 2001).…”
Section: Fulvic Acidsmentioning
confidence: 99%
“…The combined capacity of fulvic acids both to chelate nutrients such as Fe and move through membranes has suggested the fulvic acids may play similar roles as natural chelators in the mobilization and transport of Fe and other micronutrients (Bocanegra et al 2006). It has also been suggested that since they have smaller molecular weights, FAs can remain in soil solution even at high salt concentrations and at a wide range of pH (Zimmerli et al 2008;Zhuang et al 2007;Zhang et al 2010;Zhang & Ervin 2008;Zhang & Ervin 2004;Zhang et al 2006). Therefore they have long-lasting potential to interact with plant roots (Varanini and Pinton 2001).…”
Section: Fulvic Acidsmentioning
confidence: 99%
“…Phytohormones, e.g. auxins (Dimpka et al, 2008), cytokinins (Zhang and Ervin, 2008), ethylene (Tamaoki et al, 2008), ABA (Kurepin et al, 2008) are also known to confer stress protection in plants. Additionally, brassinosteriods (Clouse, 2008) and polyamines (Tassoni et al, 2008) are actively involved in stress management.…”
Section: Introductionmentioning
confidence: 99%
“…These organic formulations contain all the trace elements and some essential plant growth hormones (Zhang and Ervin, 2008). Natural plant growth regulators (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Natural plant growth regulators (e.g. Auxin, Gibberellin and cytokinin) present in these liquid organic formulations give a major boost to crop yields by accelerating the plant's metabolic function (Zhang and Ervin 2008). The recommended dose of fertilizer was taken as 120 kg N/ha, 60 kg P/ha, 40 kg K/ha.…”
Section: Introductionmentioning
confidence: 99%